Colorado water, January/February 2014 - Middleton, Lindsey A., editor; Colorado Water Institute, publisher (Colorado State University. Libraries, 2014)
Newsletter of the Colorado Water Center. Special edition: South Platte groundwater.
The newsletter is devoted to enhancing communication between Colorado water users and managers and faculty at the state's research universities.
Keywords: Water resources development -- Colorado; Water use -- Colorado; Water-supply -- Colorado; Water-supply -- Management -- Colorado